EFEKTIVITAS MODEL REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Putratawa, Tegar; Yeni Dwi Kurino; Dede Salim Nahdi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of the Realistic Mathematics Education (RME) model in improving elementary school students’ motivation and mathematics learning outcomes through a Systematic Literature Review (SLR) approach. This study was conducted by adapting the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The articles analyzed were obtained from Google Scholar, Garuda, and various national and international journals that are fully accessible. Article criteria included journal articles published between 2020 and 2026, discussing the application of Realistic Mathematics Education (RME) or Indonesian Realistic Mathematics Education (PMRI) in elementary school mathematics instruction, and focusing on learning motivation, learning outcomes, conceptual understanding, critical thinking skills, or mathematical problem-solving abilities. The selection process yielded 15 articles that met the inclusion criteria. The research findings indicate that the Realistic Mathematics Education (RME) model is effective in enhancing learning motivation, learning outcomes, conceptual understanding of mathematics, critical thinking skills, and problem-solving abilities among elementary school students. These improvements occurred because Realistic Mathematics Education (RME) instruction utilizes contextual problems closely related to students’ daily lives in the learning process. Based on the research results, it can be concluded that the RME model is an effective alternative for improving the quality of mathematics education in elementary schools.